2001
DOI: 10.1097/00061198-200112000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Mutations of Axenfeld-Rieger Syndrome Caused by FOXC1 Gene in Japanese Patients

Abstract: Four different FOXC1 mutations were found in four of six Japanese pedigrees with Axenfeld-Rieger syndrome. This was a new mutation in two pedigrees that was not found in earlier generations. This study confirms that mutations in this gene cause maldevelopment of the anterior segment of the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…In 3 of the 4 families, a FOXC1 mutation was present in the mothers of the index cases, who had corectopia and iris hypoplasia, but without glaucoma. This report indicated that younger generations may have more severe symptoms than their parents' generation [13]. This feature is similar to our case.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In 3 of the 4 families, a FOXC1 mutation was present in the mothers of the index cases, who had corectopia and iris hypoplasia, but without glaucoma. This report indicated that younger generations may have more severe symptoms than their parents' generation [13]. This feature is similar to our case.…”
Section: Discussionsupporting
confidence: 90%
“…These different clinical courses might suggest that the disease is more severe in the patient than in her father. Kawase et al reported 6 Japanese ARS cases in 4 families with FOXC1 mutations [13]. In 3 of the 4 families, a FOXC1 mutation was present in the mothers of the index cases, who had corectopia and iris hypoplasia, but without glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8 Genes on chromosomes 4q25 and 6p25 have been identified as PITX2 and FOXC1, respectively. 9 These are genes coding for paired-like homeo-domain and forkhead/winged-helix transcription-factor families. They are expressed in mesenchyme of drainage structure as well as in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…that in three of the four pedigrees, the sons of women with the same FOXC1 mutation had more severe glaucoma than their mothers. [6] This prompted us to perform molecular genetic analysis with informed consent. [7]…”
mentioning
confidence: 99%